Impact of a vacuum cushion on intrafraction motion during online adaptive MR-guided SBRT for pelvic and para-aortic lymph node oligometastases. (January 2021) - Werensteijn-Honingh, Anita M.; Jürgenliemk-Schulz, Ina M.; Gadellaa-Van Hooijdonk, Christa G.; Sikkes, Gonda G.; Vissers, Nicole G.P.M.; Winkel, Dennis; Eppinga, Wietse S.C.; Intven, Martijn; Raaymakers, Bas W.; Kroon, Petra S.
Highlights: Vacuum cushion immobilization reduced intrafraction motion in posterior direction. Most intrafraction motion occurred in the first 16 minutes. On an MR-linac, vacuum cushion immobilization may not be needed for single targets. Abstract: Background and purpose: Vacuum cushion immobilization is commonly used during stereotactic body radiotherapy (SBRT) to reduce intrafraction motion. We investigated target and bony anatomy intrafraction motion (translations and rotations) during online adaptive SBRT on an MR-linac for pelvic/para-aortic lymph node metastases with and without vacuum cushion. Materials and methods: Thirty-nine patients underwent 5x7 Gy SBRT on a 1.5T MR-linac, 19 patients were treated with vacuum cushion, 19 without and 1 patient sequentially with and without. Intrafraction motion was calculated for target lymph nodes (GTVs) and nearby bony anatomy, for three time intervals (pre-position verification (PV), pre-post, PV-post, relating to the online MRI scans) per treatment fraction. Results: Vacuum cushion immobilization significantly reduced anterior-posterior translations for the pre-PV and pre-post intervals, for bony anatomy and pre-post interval for GTV ( p  < 0.05). Mean GTV intrafraction motion reduction in posterior direction was 0.7 mm (95% confidence interval 0.3–1.1 mm) for pre-post interval (mean time = 32 min). Shifts in other directions were not significantly reduced. More motion occurred in pre-PV interval than in PV-post interval (mean time = 16 min for both); vacuum cushion immobilization did not reduce intrafraction motion during the beam-on period. Conclusion: A vacuum cushion reduces GTV and bony anatomy intrafraction motion in posterior direction during pelvic/para-aortic lymph node SBRT. This motion reduction was found for the first 16 min per session. For single targets this motion can be corrected for directly with an MR-linac. Intrafraction motion was not reduced during the second half of the session, the period of radiotherapy delivery on an MR-linac. Vacuum cushion immobilization may not be necessary for patients with single lymph node oligometastases undergoing SBRT on an MR-linac.